Need analysis for the development of a microcontroller instructional module programming literacy - Yusriza Mohamd Yusof; Afida Ayob; Mohamad Hanif Md Saad; Haryanti Mohd Affandi; Aini Hussain (Bulletin of Electrical Engineering and Informatics, 2020)
In the era of the IR 4.0, the use of information technology among school students is widespread but students are not proficient in computer programming. To compete in the digital world, students need to be exposed to computer programming in order to produce computer programming experts. Integrating computer programming into the school curriculum can improve students literacy of computer programming but adequate computer programming skill among teachers are quite limited. Therefore, the development of microcontroller instructional teaching module which could address this problem is needed. This development aims to develop the module using design and developmental research (DDR) approach. Need Analysis phase in DDR is discussed in this article. The phase consists of identifying the level of knowledge, attitudes and practices of teachers about microcontroller and to obtain the views and opinions of the teachers on the developmental needs of microcontroller teaching modules. The type of microcontroller and the programming language to be used in the microcontroller module also identified.The results of this study are important to ensure that the design and development of an instructional module for microcontroller education are implemented and have a positive impact on increasing the programming literacy level among secondary school children.